Organizational Culture, Transformational Leadership, and Work Motivation Driving Employee Performance - Sudirman Sudirman; Nancy Yusnita; Widodo Sunaryo (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study investigates the role of organizational culture, transformational leadership, and work motivation as strategic drivers of employee performance in an Indonesian corporate context. Conducted over seven months from September 2024 to March 2025, the research employed a quantitative design using Likert-scale questionnaires (1–5) distributed to 104 respondents, determined through the Slovin formula from a population of 140 employees. Data analysis was performed with SPSS version 21.0 through regression and correlation techniques. The findings reveal that organizational culture has a positive and significant effect on employee performance (β = 0.311; p < 0.05), transformational leadership shows a positive but statistically insignificant effect (β = 0.406; p > 0.05), and work motivation exerts the strongest positive and significant effect (β = 0.584; p < 0.05). Furthermore, organizational culture and transformational leadership significantly enhance work motivation (β = 0.317; p < 0.05; β = 0.299; p < 0.05), while their indirect effects on performance through motivation are positive but insignificant. These results underscore that organizational culture and work motivation are the most critical determinants of employee performance, whereas transformational leadership requires stronger alignment with motivational and cultural reinforcement to maximize impact. The study contributes to organizational behavior literature by providing empirical evidence from Indonesia and offers practical insights for managers seeking sustainable strategies to improve workforce performance.